Capillary-cavernous hemangioma located in the right ventricle of the heart – case report - Kozłowicz, Michał; Olszewski, Krzysztof; Stadnik, Adam; Gałczyński, Krzysztof; Krawczyk, Elżbieta; Stążka, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The incidence of primary cardiac tumors is estimated at 0.0017-0.28%. Benign tumors account for 75-80%, among which 2.8% are hemangiomas. They arise as a result of benign proli-feration of the capillaries and are rare cardiac pathology. Hemangiomas can occupy any part of the heart, but they are mostly located in ventricles. They may cause arrhythmias, congestive heart failure, an obstacle in the right ventricular outflow, pericardial effusion, dyspnea and/or chest pain after exercise and sudden death, however, most of them are asymptomatic and detected incidentally. In our article we present a case of patient who was diagnosed with a hemangioma, which was successfully removed from the right ventricle.